2021
DOI: 10.3390/jne2030024
|View full text |Cite
|
Sign up to set email alerts
|

Fourth-Order Adjoint Sensitivity and Uncertainty Analysis of an OECD/NEA Reactor Physics Benchmark: I. Computed Sensitivities

Abstract: This work extends the investigation of higher-order sensitivity and uncertainty analysis from 3rd-order to 4th-order for a polyethylene-reflected plutonium (PERP) OECD/NEA reactor physics benchmark. Specifically, by applying the 4th-order comprehensive adjoint sensitivity analysis methodology (4th-CASAM) to the PERP benchmark, this work presents the numerical results of the most important 4th-order sensitivities of the benchmark’s total leakage response with respect to the benchmark’s 180 microscopic total cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Taken together, the n th -CASAM-N and n th -CASAM-L are the only practical methods for computing response sensitivities comprehensively and accurately for large and complex models, as has been illustrated by the application [9,11] of the n th -CASAM-L to the OECD/NEA reactor physics benchmark. Illustrative paradigm applications of the n th -CASAM-N are currently being finalized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the n th -CASAM-N and n th -CASAM-L are the only practical methods for computing response sensitivities comprehensively and accurately for large and complex models, as has been illustrated by the application [9,11] of the n th -CASAM-L to the OECD/NEA reactor physics benchmark. Illustrative paradigm applications of the n th -CASAM-N are currently being finalized.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained in [9] indicated that many second-order sensitivities were much larger than the largest first-order ones (contrary to the widely held belief to the contrary, for reactor physics systems), which motivated the investigation [11] of the largest third-order and, subsequently, fourth-order sensitivities. The evident conclusions that resulted from these works [9,11] are that the consideration of only the first-order sensitivities is insufficient for making credible predictions regarding the expected values and uncertainties (variances, covariances, skewness) of calculated and predicted/adjusted responses. At the very least, the second-order sensitivities must also be computed in order to enable the quantitative assessment of their impact on the predicted model responses.…”
Section: Introductionmentioning
confidence: 86%
“…A higherorder sensitivity analysis of this model has not been performed yet. On the other hand, solvers for the computation of first-, second-, third-and fourth-order sensitivities for neutron transport models are available, as described in the works by Fang and Cacuci [12,13], where it was found that the microscopic total cross-sections of isotopes 1 H and 239 Pu of the reactor physics benchmark analyzed therein are the most important parameters affecting that benchmark's leakage response. In particular, it was shown that the largest unmixed 4th-order sensitivity is S (4) = 2.720 × 10 6 , which is with respect to the total cross-section σ 30 t,6 for the 30th energy group (which comprises thermalized neutrons in the energy interval from 1.39 × 10 −4 eV to 0.152 eV) of isotope 6 (i.e., 1 H).…”
Section: Discussionmentioning
confidence: 99%
“…The accompanying work [4], which is designated as Part I, has reported the exact computation of the most important 4th-order sensitivities of the PERP benchmark's total leakage response with respect to the benchmark's 180 group-averaged microscopic total cross sections. The 4th-order sensitivities obtained in [4] are used in this work to compute the contributions of the 4th-order terms, and compare their impact on the leakage response's expected value, variance and skewness with the corresponding impact stemming from the 1st-, 2nd-and 3rd-order sensitivities.…”
Section: Introductionmentioning
confidence: 99%
“…where JTX = G × I = 180 denotes the total number of microscopic total cross sections for G = 30 groups and I = 6 isotopes contained in the PERP benchmark [4].…”
mentioning
confidence: 99%